ORGANIC MATTER IN HYDROTHERMAL METAL ORES AND HYDROTHERMAL FLUIDS - Orem W.H.; Spiker E.C.; Kotra R.K. (My University, 1990)
Massive polymetallic sulfides are currently being deposited around active submarine hydrothermal vents associated with spreading centers. Chemoautolithotrophic bacteria are responsible for the high production of organic matter also associated with modern submarine hydrothermal activity. Thus, there is a significant potential for organic matter/metal interactions in these systems. We have studied modern and ancient hydrothermal metal ores and modern hydrothermal fluids in order to establish the amounts and origin of the organic matter associated with the metal ores. Twenty-six samples from modern and ancient hydrothermal systems were surveyed for their total organic C contents. Organic C values ranged from 0.01% to nearly 4.0% in these samples. Metal ores from modern and ancient sediment-covered hydrothermal systems had higher organic C values than those from modern and ancient hydrothermal systems lacking appreciable sedimentary cover. One massive pyrite sample from the Galapagos spreading center (3% organic C) had stable isotope values of −27.4% (δ13C) and 2.1% (δ15N), similar to those in benthic siphonophors from active vents and distinct from seep sea sedimentary organic matter. This result coupled with other analyses (e.g. 13C NMR, pyrolysis/GC, SEM) of this and other samples suggests that much of the organic matter may originate from chemoautolithotrophic bacteria at the vents. However, the organic matter in hydrothermal metal ores from sediment covered vents probably arises from complex sedimentary organic matter by hydrothermal pyrolysis. The dissolved organic C concentrations of hydrothermal fluids from one site (Juan de Fuca Ridge) were found to be the same as that of background seawater. This result may indicate that dissolved organic C is effectively scavenged from hydrothermal fluids by biological activity or by co-precipitation with metal ores.